The Necessity of Updating the Classification of Sciences for our Time - Cao Dam, Vu (VNU Journal of Science: Policy and Management Studies; Vol 38 No 1, 2022)
Nowadays, the classification of sciences was originated from the ideas of classification of sciences, demonstrated in Engels Dialectics of Nature, written from 1870 to 1882. Basing the ideas of Dialectics of Nature, Kedrov, a Soviet philosopher of Science had elaborated a classification of sciences and demonstrated in a workshop on Philosophy of Science in Zurich in 1954. Following the Kedrov proposal, UNESCO had suggested a classification of sciences, that is well-known in our time. It has been nearly a century and more from Engels' Dialectics of Nature to our modern society. Many new scientific disciplines are known in our system of contemporary knowledge, for example, Systems Theory, Game Theory, Theory of Mass Service, Theory of Optimisation, Management Science, and so on. It is necessary to update the classification of sciences for our time. In 1964, R. Caude and Moleroupe d’etudes methodologiques of CNOF (France) published a very interesting book titled “Methodologie vers une science de l’Action” – A new scientific discipline that did not exist in the Engels ideas of Dialectics of Nature, neither in Kedrov’s proposal of classification of sciences in 1954. Regarding the methodological approach to update the UNESCO classification of science, we must certainly rely on the Engels approach on the “connection” of sciences in Dialectics of Nature. Keywords Classification of sciences, UNESCO, Vietnam National University, Update, Dialectics of Nature, Engels, Kedrov, New Scientific Disciplines after Engels’ Dialectics of Nature. References [1] B. Kedrov, Classification des Sciences, Edition Progress, Moscow, 1978, Vol. 1-2. [2] R. C. E. Moles, Groupe d’Etudes Methodologiques de CNOF, Methodologie vers Une Science de l’Action, Entreprise Moderne d’Edition, Paris, 1964.